â€“ED FORMS DALAM ARTIKEL JURNAL ENGLISH TEACHING FORUM VOLUME 43 NO.4 TAHUN 2005 - Onibala, Monalisa S. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research entitled â€œ-Ed Forms in Journal Article of English Teaching Forum Volume 43 Number 4 Year 2005â€ by Pham HoaHiep, Bulent Alan and Fredricka L. Stoller: A Syntactical Analysis. This research is aimed identifying, classifying and analyzing the â€“ed form used in the journal article. Based on the types of the â€“ed forms the data collected from the journal articles were classified and analyzed according to the concept of Foley dan Hall (2003), Phillips (2000), Azar (2003), Aarts dan Aarts (1982). And based on the functions used the concept by Lado (2008) and Swam (1995). The result shows that there are five types of â€“ed forms used in the journal articles, namely; -ed forms in the present tense (14 data), -ed forms in passive voice (84 data), ed formsin past tense (29 data), -ed forms in participle adjective (92 data), â€“ed forms in subject implicit (20 data). The total â€“ed forms found in journal are 239 data. In this research, it is found that â€“ed form has two functions: the â€“ed form as verb and the â€“ed form as adjective. Â Key words: -ed Form, Past Participle and Past Tense, Journal